PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), RETURN ON EQUITY (ROE), DAN TOTAL ASSET TURNOVER (TATO) TERHADAP HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DIBEI TAHUN 2017-2021 - Mandager, Umbu Ali Muksin; Hidayati, Siti Aisyah; Ardhana Putra, I Nyoman Nugraha (Jurnal Magister Manajemen, 2023)
This research is entitled The Effect of Current Ratio (CR), Debt to Equity Ratio (DER), Return On Equity (ROE), and Total Asset Turnover (TATO) on Stock Prices of Food and Beverage Companies Listed on the IDX in 2017-2021. Aims to partially test the effect of the Current Ratio (CR), Debt to Equity Ratio (DER), Return On Equity (ROE), and Total Asset Turnover (TATO) on the Stock Prices of Food and Beverage Companies Listed on the IDX. The population of this research is 72 companies. Sampling was carried out using the purposive sampling method, and obtained a sample of 15 food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The data used in this study is secondary data in the form of company financial reports published on the Indonesia Stock Exchange. The research data analysis procedure uses Variable Description Analysis, Descriptive Statistical Analysis, Classical Assumption Test, Multiple Regression Analysis, Model Feasibility Test, Hypothesis Test and Detemination Test (Adjusted R2)This research is entitled The Effect of Current Ratio (CR), Debt to Equity Ratio (DER), Return On Equity (ROE), and Total Asset Turnover (TATO) on Stock Prices of Food and Beverage Companies Listed on the IDX in 2017-2021. Aims to partially test the effect of the Current Ratio (CR), Debt to Equity Ratio (DER), Return On Equity (ROE), and Total Asset Turnover (TATO) on the Stock Prices of Food and Beverage Companies Listed on the IDX. The population of this research is 72 companies. Sampling was carried out using the purposive sampling method, and obtained a sample of 15 food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period.The data used in this study is secondary data in the form of company financial reports published on the Indonesia Stock Exchange. The research data analysis procedure uses Variable Description Analysis, Descriptive Statistical Analysis, Classical Assumption Test, Multiple Regression Analysis, Model Feasibility Test, Hypothesis Test and Detemination Test (Adjusted R2) The results of the study prove that Current Ratio (CR) has a negative and not significant effect, Debt to Equity Ratio (DER) has a negative and not significant effect, Return On Equity (ROE) has a positive and significant effect and Total Asset Turnover (TATO) has a negative and significant effect on Price Food and Beverage Company Shares 2017-2021